Five ideas on the formation of the jurist of the mid-21st century - Atienza, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The five ideas revolve around whether the university is going to be able to continue to be the center of the jurist´s education, what changes should be introduced for this and the role that the philosophy of Law and legal argumentation should play.
Keywords: Law teaching; legal culture; university crisis